Estructura organizacional de la oficina de estadística para la Municipalidad Distrital de Chicama - Paz Rubio, Deyanira Elizabeth (2013)
This paper titled "ORGANIZATIONAL STRUCTURE OF THE BUREAU OF STATISTICS FOR THE DISTRICT MUNICIPALITY OF CHICAMA", is how you should organize and implement a statistical office in Chicama district municipality is located north of the city of Trujillo, this district has 9 towns and 07 settlements and by not having in its establishment that office that is responsible for controlling the statistical information generated in their areas. Given this reality was made a diagnosis, finding that there is no statistical office, located only one responsible for the personnel office, which has the sole function control staff assistance, channels it through a few formats that have been developed for such end._x000D_ It is recommended that the municipality of Chicama establishing a statistical office to raise the mechanisms and procedures for systematically in each area to determine the actual demand for the information and is directed by a competent professional or specialist branch